Protein contents and metal composition of some feed crops from Turkey - Ciftci, Harun; Bagci, Eyup (My University, 2009)
In this study, trace elements and protein contents of some feed crops (Medicago sp.) from Turkey were investigated. Inductively coupled plasma-optical emission spectrometry (ICP-OES) technique was used to determine elemental concentrations of major and trace elements in Medicago sativa L., M. minima (L.) var minima, M. rotata Boiss. var. eliezeri, M. rigidula (L.) var. rigidula and Melilotus alba Desr. (Fabaceae) species. This feed crops samples were digested by microwave system and analyzed. Nine elements (Cu, Mn, Cr, Ni, Zn, Fe, Mg, Al and Pb) were detected. Protein contents were determined between 18.40-45.54 percentage in the seed. The results showed that M. minima var. minima's seeds are a good source of essential and beneficial micronutrients required for healthy growth.
Keywords: Fabaceae; Feed crops; ICP-OES; Medicago; Protein; Trace elements